Skin cancer knowledge, attitude and behavior towards sun exposure among young adults in Lithuania - Ieva Laniauskaitė; Agnė Ožalinskaitė; Rasa Strupaitė; Matilda Bylaitė (Our Dermatology Online, 2011)
Objective: The aim of the study was to assess young adult's knowledge about skin cancer and it's risk factors, attitude towards sun exposure and the interactions of various behaviors in the sun.Material and methods: The anonymous questionnaire-based inquiry of 750 respondents was created according to the anonymous form filled-in during the annual Euromelanoma Day campaign. Results: 708 questionnaires were filled-in correctly: 328 (46.3%) by men, 380 (53.7%) by women. Median of age was 21 (women - 22, men - 21). During the sunny days 93.2% of respondents sometimes seek shade, 17.5% of young adults never try to get a tan from 11a.m. to 3p.m. Sunglasses are worn in 52.4% of cases, however 63.1% of them with UV filters. 8,1% of respondents always wear T-shirts, 30.6% cover head in the beach. While sun-bathing one third (32.9%) wear sun protection cream, while working or doing sports outdoors - 8.9%. Majority (57.4%) apply sun protection cream when coming to the beach, 31.4% of them don't use it repeatedly. Those who knew, what is melanoma, were more likely to wear sunglasses (p=0.003) with UV filters (p=0.006), T-shirts (p=0.046), covered head (p<0.0001) and seeked shadow (p=0.002) on the beach; used sun protection cream while working ≥1 hour outdoors (p=0.001) or sunbathing (p<0.0001), and choosed a sun protection cream according to SPF value (p<0.0001).Conclusion: The data of this study showed that respondents behave careless in the sun. One third of respondents always wear sun protection cream, the majority do not know how to use it properly. More responsible behavior in the sun depends on better knowledge of skin cancer.